Selection and biophysical characterization of DARPins - Payne, Iida (My University, 2024)
In the past decades antibodies have been a real success story treating variety of diseases. Development started from murine monoclonal antibodies and have continued all the way to multispecific all human antibodies. However, antibodies have limitations and multispecifics are challenging to develop due to misspairing chain problem. The solution could lie in alternative scaffolds, such as Designed Ankyrin Repeat Proteins (DARPins). DARPins are small 15 kDa single polypeptides without disulfide bridges and glycosylations. The aim of this project is to study what type of epitopes can DARPins recognize and bind by using phage display method. Selected target is model antigen mCherry coupled with Avi,- alpha,- streptwin- and histidine tags. Eight antigen recognizing DARPins were found. However, selections targeting histidine tail were unfortunately unsuccessful. Selected DARPins were expressed in single and tethered form in microbial expression system and characterized for affinity and stability. All of the eight selected single anti-mCherry DARPins had nanomolar level affinitys whereas tethered DARPins reached up to picomolar levels. The highest melting temperature of selected DARPin is 79.5 C°, being equal to published state-of-art DARPins. Selections, expression and tethering DARPins have proven to be relatively effortless and inexpensive. These results are promising and suggesting that DARPins are a prominent candidate for drug development. With this in mind, there is no surprise that multiple DARPins are currently under development for different applications and treatment of various diseases.
Keywords: DARPin, phage display, multispecific therapeutics